2014
DOI: 10.1111/eea.12182
|View full text |Cite
|
Sign up to set email alerts
|

Development of the gregarious ectoparasitoid Nasonia vitripennis using five species of necrophagous flies as hosts and at various developmental temperatures

Abstract: The utility of five species of necrophagous flies (Diptera) as pupal hosts for Nasonia vitripennis (Walker) (Hymenoptera: Pteromalidae) was examined by comparing incidences of parasitism, fecundity, and several features of wasp development at three rearing temperatures. Species differences in host suitability were evident in all life history features examined, with the highest incidences of parasitism, largest clutches and adult body sizes, and shortest periods of development occurring when the sarcophagid Sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…But for P. digoneutis, no positive relationship was found A c c e p t e d M a n u s c r i p t between longevity and female body size, nor any between lifetime fecundity and female body size (Haye et al, 2005). Moreover, host suitability (Rivers & Losinger, 2014) and temperature (Bazzocchi, Lanzoni, Burgio & Fiacconi, 2003) significantly affected female body size, and temperature showed an inverse relationship with body size (Bürgi & Mills, 2013). Our study found that hind tibia length of female P. spretus offspring decreased significantly with increasing rearing temperature from 15 to 27 °C, with no significant difference between 15 and 19 °C.…”
Section: Peristenus Spretus May Play An Important Role In Biological mentioning
confidence: 54%
“…But for P. digoneutis, no positive relationship was found A c c e p t e d M a n u s c r i p t between longevity and female body size, nor any between lifetime fecundity and female body size (Haye et al, 2005). Moreover, host suitability (Rivers & Losinger, 2014) and temperature (Bazzocchi, Lanzoni, Burgio & Fiacconi, 2003) significantly affected female body size, and temperature showed an inverse relationship with body size (Bürgi & Mills, 2013). Our study found that hind tibia length of female P. spretus offspring decreased significantly with increasing rearing temperature from 15 to 27 °C, with no significant difference between 15 and 19 °C.…”
Section: Peristenus Spretus May Play An Important Role In Biological mentioning
confidence: 54%
“…More significant than size or period of activity on carrion is that the life history characteristics of most parasitoids, other than the pteromalid Nasonia vitripennis (Walker), that frequent carrion have not been examined or only limited aspects of the biology and behavior of a few species are known [26,27]. For example, developmental thresholds and temperatureinfluenced developmental data have been worked out for only two parasitoids, N. vitripennis and Tachinaephagus zealandicus Ashmead (Hymenoptera: Encyrtidae) [28][29][30][31]. Even less is known about seasonal occurrences of parasitoids, with the most extensive work being conducted on N. vitripennis and to a much lesser extent with T. zealandicus and Alysia manducator (Panzer) (Hymenoptera: Braconidae) [29,[31][32][33][34], and the parasitoid fauna of most biogeographical regions has never been examined [35][36][37].…”
Section: Parasitic Hymenoptera As Alternate Forensic Indicator Speciesmentioning
confidence: 99%
“…These insects are parasitoids of necrophagous blowfly (Diptera: Calliphoridae) and fleshfly (Diptera: Sarcophagidae) pupae [1][2][3][4][5][6]. Adult wasps have a well-developed sense of smell, and females can locate blowfly pupae hidden in the soil or under shelters [3].…”
Section: Introductionmentioning
confidence: 99%
“…The wasps lay eggs inside the puparium, and the larvae develop by feeding on the living fly nympha. After several days, 10-40 young adult wasps emerge from the puparium, ready to start a new generation [1,2,7]. In forensic entomology laboratories, they are usually introduced with contaminated puparia sampled in the field, but direct contamination by adult wasps is also frequent.…”
Section: Introductionmentioning
confidence: 99%